Chapter 41: Tomato Production in Florida - Stephen M. Olson; William M. Stall; Timur M. Momol; Susan E. Webb; Timothy G. Taylor; Scott A. Smith; Eric H. Simonne; Eugene McAvoy (EDIS)
This document is HS739, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.